THE INFLUENCE OF ORGANIZATIONAL CULTURE, COMPETENCE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE DIRECTORATE OF HIGH SCHOOLS IN THE MINISTRY OF EDUCATION, CULTURE, RESEARCH AND TECHNOLOGY OF THE REPUBLIC OF INDONESIA - Dian Pangarso; Maswanto Maswanto; Cece Haryoto (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This research aimed to detect the relationship between organizational culture, competence and motivation on employee performance at The Directorate Senior High Schools, Directorate General of Pre-School Dikdasmen, Ministry of Education Culture Research and Technology Republic of Indonesia. This study applies an associative method with a quantitative approach. Data was obtained by observing, interviewing and distributing questionnaires to 75 employees who were sample saturated since the population was less than 100. The analysis methods used is multiple linear regression to test the effect of independent variables (organizational culture, competence, and motivation) on the dependent variable (performance). Findings revealed that organizational culture, competence and motivation altogether had significant influence over employee performance. Validation and reliability tests for the questionnaire indicated that the instruments are valid as well as reliable while normality, heteroscedasticity, multicollinearity demonstrate that the regression model used met basic statistical assumptions hence suitable for further testing. Thus, bettering organizational culture; improving individual competences; enhancing motivation are going to have a substantial impact on employee’s behavior at work which in turn will improve their productivity considerably.